2012
DOI: 10.1038/ismej.2012.129
|View full text |Cite
|
Sign up to set email alerts
|

Environmental distribution of coral-associated relatives of apicomplexan parasites

Abstract: A lineage of plastid-bearing eukaryotic microbes that is closely related to apicomplexan parasites was recently found in a specific association with coral reefs (apicomplexan-related lineage-V, or ARL-V). Here, we address the possible nature of this association using plastid 'contamination' in fine-scale bacterial sequence surveys. In a transect between corals and associated macroalgae, ARL-V is specifically associated with the coral, in contrast to all microalgal types (including diatoms, haptophytes, pelagop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…Previous 16S studies of corals have shown that coral symbionts such as Symbiodinium dinoflagellates48 are present within the coral tissue (mesenteries) for at least part of their life cycle, as do the apicomplexan parasites/Chromerida4950, but these cells are not present in the calcium carbonate skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…Previous 16S studies of corals have shown that coral symbionts such as Symbiodinium dinoflagellates48 are present within the coral tissue (mesenteries) for at least part of their life cycle, as do the apicomplexan parasites/Chromerida4950, but these cells are not present in the calcium carbonate skeleton.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial community assays are known to recover rRNA gene sequences that do not represent extant bacteria but rDNA copies encoded by chloroplast DNA of eukaryotes with chloroplasts or non-photosynthetic plastids [15,16]. Within Bac1 data, we recovered chloroplast/plastid small-subunit rRNA gene belonging to an apicomplexan clade ARL-V clade [15,16] in all 4 coral DNA (abundance 0.3%, 3.7%, 0.2% and 1.0% in sequences from A .…”
Section: Resultsmentioning
confidence: 99%
“…Within Bac1 data, we recovered chloroplast/plastid small-subunit rRNA gene belonging to an apicomplexan clade ARL-V clade [15,16] in all 4 coral DNA (abundance 0.3%, 3.7%, 0.2% and 1.0% in sequences from A . palifera 42a, M .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromera velia has been isolated from and detected in coral tissue and has been experimentally demonstrated to infect coral larvae (Moore et al ., ; Cumbo et al ., ; Janouškovec et al ., ; Šlapeta & Linares, ). The coral holobiont is a nutrient‐rich system involving complex interactions between the predominant coral host and symbiotic zooxanthellae partners together with a poorly defined milieu of associated microorganisms such as bacteria, viruses and eukaryotes, including C. velia (Bourne et al ., ; Janouškovec et al ., ). Chromera velia occupies a significant phylogenetic position as an evolutionary link between dinoflagellates and apicomplexans.…”
Section: Introductionmentioning
confidence: 99%